2012
DOI: 10.1111/j.1600-079x.2012.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of MT1and MT2melatonin receptors differentially abrogates the development and expression of methamphetamine‐induced locomotor sensitization during the day and the night in C3H/HeN mice

Abstract: This study explored the role of the melatonin receptors in methamphetamine (METH)-induced locomotor sensitization during the light and dark phases in C3H/HeN mice with genetic deletion of theMT1 and/or MT2 melatonin receptors. Six daily treatments with METH (1.2 mg/kg, i.p.) in a novel environment during the light phase led to the development of locomotor sensitization in wild-type (WT), MT1KO and MT2KO mice. Following four full days of abstinence, METH challenge (1.2 mg/kg, i.p.) triggered the expression of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
1
23
1
Order By: Relevance
“…The trend in all groups showed locomotor activity increasing across trial days, with significant locomotor sensitization observed in WT and MT 1 KO mice at ZT 6–8. This is consistent with our previous finding demonstrating a diurnal variation in METH–induced locomotor sensitization in C3H/HeN mice [12]. Thus we conclude that the effects of melatonin receptor deletion and time of day are specific to METH-induced reinforcing behaviors, as neither of these factors significantly altered the locomotor stimulant properties of METH at the dose tested.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The trend in all groups showed locomotor activity increasing across trial days, with significant locomotor sensitization observed in WT and MT 1 KO mice at ZT 6–8. This is consistent with our previous finding demonstrating a diurnal variation in METH–induced locomotor sensitization in C3H/HeN mice [12]. Thus we conclude that the effects of melatonin receptor deletion and time of day are specific to METH-induced reinforcing behaviors, as neither of these factors significantly altered the locomotor stimulant properties of METH at the dose tested.…”
Section: Discussionsupporting
confidence: 93%
“…Assessments were systematically conducted between ZT 6–8 and ZT 19–21, corresponding to the peak and trough of melatonin respectively [10]. Comparisons were made among genotype and between two times of day using a METH dose of 1.2mg/kg, which produces robust sensitization in the C3H/HeN mice [12]. These controls allow for accurate conclusions on the effect of melatonin receptor genotype and time of day at a single dose of METH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations